IMPROVEMENT OF CONCRETE ROAD INFRASTRUCTURE IN WULUHAN DISTRICT - Indra Nurtjahjaningtyas; Anita Trisiana; Luthfi Amri Wicaksono (UNEJ e-Proceeding, 2022)
Infrastructure improvements are needed to accelerate the pace of the economy. The impact of Covid-19 has recently reduced the quality of infrastructure due to reduced community mobility. To improve infrastructure, especially roads, proper planning is needed according to existing regulations. State apparatus at the local level is expected to be able to prepare good road planning. The use of concrete roads is suitable for some areas that are far from the city because of low maintenance costs. In the Wuluhan District, there are several obstacles so that this service is expected to increase knowledge about concrete road planning. The output of this service is an understanding of concrete road planning in accordance with PU Bina Marga regulations. Keywords: Construction, Technical, Road, Concrete, Wuluhan, Jember.